Geography of tourism - the ecological crisis as an objective criticism of labor. Tourism as a "necessary illusion" - Anselmo Alfredo (GEOUSP: Espaço e Tempo, 2001)
In this article we intended to develop a methodological analytical perspective about tourism in a way to remain contrary to the "promoting" thinking expectatives that wants to solve what it faces as problems, instead of understand the determinations of the real. Anyway, in our expectative, it becam e possible consider the tourism as a fenomenom that reveals a modern and contemporary relation between society and nature, where the last one from presupposition of the social process becomes to the condition of product, realising itself as fetish, what includes the hiding of the contradictions that refer to the sam e relation. In our point of view the tourism acts in the free time realising it as productive time, fetishising nature and the natural notion, in a way that tourism behaviours itself as a necessary illusion. Necessary because permits the continuity of the contradiction we've already said. That's why we have an opposite expectative to the other one, related to the strategies that promote the tourism as a business. To realise our methodological way we consider both logical and historical determinations, that composite the division of this article